Converting a tourist destination into a brandDepending on the cognitive image of the destination Case Study: Lattakia Governorate - القرحيلي لين; أحمد السكّري (Latakia University Journal - Economic and Legal Sciences Series, 2023)
This study aimed at tourism in Istanbul, in order to achieve the goal of this study, a question divided into parts, in order to collect data, select a random sample of tourists who visited Lattakia Governorate,To achieve the aim of the study, the researcher designed a questionnaire consisting of (13) questions divided into four parts, in order to collect data. A valid questionnaire for statistical analysis. The study reached several results, the most important of which are:- There is a statistically significant relationship to the cognitive image of the tourist destination on the choice of this destination.- The presence of a statistically significant relationship to the cognitive image of the tourist destination on the intention to re-visit it.- There is a statistically significant relationship to the cognitive image of the tourist destination to recommend this destination. And those relationships were strong relationships with a positive trend. The study also found the possibility of applying the concept of transforming the tourist destination into a brand in Lattakia Governorate, by working to improve the cognitive image of that destination in order to positively influence the behavior of tourists.